استخدام نموذج التّعليم Student Team Achievement Division في تعليم مهارة كتابة الطلاب في المدرسة التربية الإسلامية سالاريح أيّا أغام - Suci Wulandari; Oktarina Yusra; Nur Hasanah; Al Baihaqi Anas (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The researcher found issues in teaching writing skill to students in the eighth semester of Islamic Education School Selaras Air, Agam. Teachers still explain the subject using the traditional teaching model, students have low motivation such as low desire to learn the Arabic language, low activity in following the teaching process, low enthusiasm in teaching the Arabic language, low effort in doing tasks independently, and students' laziness in following the teaching process. The researcher uses a quantitative research with a quantitative empirical research type. The research population is 47 students, and the sample size is 47 students. The researcher uses Purposive Sampling. The method of data analysis is statistical analysis using the SPSS program. The results of the research are that there is an effect of using the Student Team Achievement Division model in teaching students' writing skills, and the effect size is about 64.53%. The mean score of the posttest in the experimental class was 84.06 and in the control class was 71.33. The researcher found that the significant result or Sig. (2-tailed) in the hypothesis test is 0.002, which is smaller than 0.005. Therefore, the null hypothesis is rejected (Ho) and the alternative hypothesis is accepted (Ha). This indicates that there is a mean difference between the experimental and control classes in teaching the skill of writing.